Analysis of Garbage Classification and Processing Methods Based on Text Mining Technology - Tian, Yunan; Jiang, Ling (International Journal of Computer Science and Information Technology, 2023)
This article focuses on the current situation of garbage classification and uses text mining technology to explore suggestions for the future development of garbage classification from the perspective of the public. Subsequently, sentiment analysis based online public opinion analysis is used for garbage classification. At the end of the article, based on the above analysis, we draw conclusions on the attention of online public opinion and public sentiment, and propose scientific suggestions for the development of garbage classification from three levels: government, community, and individuals, in order to promote public participation in garbage classification.